Failure to seroconvert after three doses of inactivated COVID-19 vaccines in a patient co-infected with HBV and HIV: A case report. Issue 6 (30th November 2022) - Zeng, Guang; Tang, Jie; Feng, Shuidong; Xu, Liumei; Wang, Xiaohui; Yang, Zhengrong
ABSTRACT: In the global context of the COVID-19 pandemic, the overall benefits of getting any COVID-19 vaccine approved by the World Health Organization for emergency use outweigh the potential risks, even in people with weakened immune systems, including people living with HIV (PLWH). At present, there are no reports of HIV/hepatitis B virus (HBV) co-infected patients receiving a booster dose of the inactivated COVID-19 vaccine. Here, we describe a patient with HIV/HBV co-infection who did not seroconvert to three doses of the inactivated COVID-19 vaccine.